PRELIMINARY EXPERIMENTAL STUDY ON DESIGNING BALLAST SYSTEM FOR AUTONOMOUS UNDERWATER VEHICLE - Teguh Herlambang; Subchan Subchan; Hendro Nurhadi (JOURNAL ASRO, 2019)
ABSTRACT Unmanned submarine commonly called Autonomous Underwater Vehicle (AUV) is one type of underwater robots used for underwater mapping. AUV is an underwater vehicle capable of automatically moving in water, controlled by humans on vessel. To build AUV is not easy as many components play important roles in the operation of AUV, one of which is active ballast. Calculations on the making and benchmarks of active ballast systems are still very rare. Active ballast is a set of equipment used to fill its tanks with seawater and to empty sea water from the tanks on submarines. These tanks are intended to balance submarines and for active ballast systems on submarines so as to be able to dive and float as needed. In this paper an experimental study was carried out on a tube resembling AUV with both fresh water and sea water to obtain ballast volume in AUV. Keywords: AUV, Active ballast, Experimental study